Marketing Strategies and Operations of Wholesalers that Affect Success in Managing Fruit and Vegetable Market in Western Thailand. - Malaikaew, Ratree (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
The objective of this research were to study 1) the marketing strategies of wholesale traders in the Central Fruits and Vegetables Market in Western Thailand, 2) the operation of wholesale traders in the Central Fruits and Vegetables Market in Western Thailand, 3) the success in the fruit and vegetable marketing business in the Central Fruits and Vegetables Market in Western Thailand, and 4) the marketing strategies and operations of wholesalers affect to the success in the fruit and vegetable marketing business in the Central Fruits and Vegetables Market in Western Thailand. The research samples were 309 wholesale traders in the Central Fruits and Vegetables Market in Western Thailand. The research tool was a questionnaire, rating scales and statistics. The data were analyzed by using frequency, percentage, mean, standard deviation, and multiple regression analysis by Enter. The research results were as follows: 1. The marketing strategies of wholesale traders in the Central Fruits and Vegetables Market in Western Thailand were overall at a highest level, the first order of product, ranked in descending order of price, promotion, creation and physical, place, process and person, respectively. 2. The operation of wholesale traders in the Central Fruits and Vegetables Market in Western Thailand were overall at a high level, the first order of reactive strategy, ranked in descending order of critical point planning, complete planning, and opportunistic strategy, respectively. 3. The success in the fruit and vegetable marketing business in the Central Fruits and Vegetables Market in Western Thailand were overall at a high level, the first order of cost efficiency, ranked in descending order of social responsibility, profitability, physical resources, innovation, financial resources, human resources, quality, and marketing status, respectively. 4. The marketing strategies were product, price, place, promotion, process, person, and creation and physical affect to the success in the fruit and vegetable marketing business in the Central Fruits and Vegetables Market in Western Thailand statistical significance at the 0.01 level, and predictive equation form was Y = 3.774 + 0.011X1 + 0.049X2 + 0.054X3 + 0.091X4 + 0.015X5 + 0.016X6 + 0.118X7. When operations of wholesale traders in the central fruits and vegetables market in western Thailand, were complete planning, critical point planning, opportunistic strategy, and reactive strategy effect on the success of the fruit and vegetable market in western Thailand, statistically significant at the 0.01 level, and predictive equation form was Y = 3.088 + 0.013X8 + 0.004X9 - 0.021X10 + 0.155X11. Article history : Received 20 July 2018 Revised 7 October 2018 Accepted 17 October 2018 SIMILARITY INDEX = 0.00